Pengaruh Kualitas Audit, Audit Tenure, Opini Audit Sebelumnya Dan Pertumbuhan Perusahaan Terhadap Audit Going Concern (Studi Empiris Perusahaan Manufaktur Terdaftar di Bursa Efek Indonesia Periode 2011-2014) - , Mahdi, Drs.Wahyono, Ak,MA (2017)
This study aims to analyze the factors that affect the going concern audit covering audit quality, audit tenure, the previous audit opinion and the company's growth. This research was conducted through secondary data searches and using 68 samples from the list of manufacturing companies in Indonesia Stock Exchange during the period 2011, 2012, 2013, 2014. Logistic regression analysis was used as techniques in this study to test the hypothesis. From the processed data can be concluded that only the variable quality of the audit and audit opinion the previous year affecting the going-concern audit and variables that do not affect the going concern audit opinion is audit tenure and the company's growth.